Pengembangan Sistem Informasi Pencatatan dan Pelaporan Gizi Balita - Timothy Julian; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Posyandu is a health service facility that has the objective to provide health services for the local society, especially for mothers, babies, and toddler. However, based on the interview with one of the nutrition lecturers from FK UB, and with the midwife in charge at Krebet Village, Malang Regency, followed by observation on one of the Posyandu at Krebet Village, Malang Regency, there were several problems found at the Posyandu and on the midwife itself. Because of the process of recording of the health services at the Posyandu is still done manually, and still using many different documents, making the process of recording and making nutrition reports by the midwife vulnerable to mistakes and inorganization. This problem can lead to more mistakes, like for the children's health indication mistake in that area. To solve this problem, a web-based information system using waterfall SDLC and object-oriented approach was developed. On the requirements analysis phase, produced 4 actors, 33 functional requirements, and 1 non-functional requirements. From the results the requirements analysis phase, the design and implementation process using object-oriented approach carried out. The testing phase conducted using validation testing got the score of 100 % valid, as well as the user acceptance test (UAT) to 5 users got the score of 97.1 % acceptance rate, which means that the users strongly agrees to the system that has been made.